Annular skin lesions in childhood: Review of the main differential diagnoses - Diana Narváez; Beatriz Di Martino Ortiz; Mirtha Rodríguez Masi (Our Dermatology Online, 2017)
Figurate skin eruptions are fixed or migratory lesions, which is clinically characterized by annular circinate, arcuate, targetoid or polycyclic plaque. Although most skin lesions typical annular are dermatophytosis (ringworm), general practitioners and especially pediatricians have to consider other possible diagnoses. Tinea corporis often can be diagnosed based on a direct positive test with potassium hydroxide. Topical and systemic antifungal are usually curative. Pityriasis rosea is characterized by small lesions, light erythematosus colored, distributed along the lines of division of the skin. Treatment is symptomatic. Granuloma annulare is characterized by annular plaques with non-squamous indurated edges, usually in the extremities. Half of the cases resolve spontaneously within two years. Hansen's disease may present with similar body ringworm plates by submitting one or more annular lesions. Urticaria, that may affect 10 to 20 percent of the population, is presented with evanescent annular plates with no scales. The subacute cutaneous lupus erythematosus may occur in a ring on sun-exposed areas as well as Papulosquamous form. Erythema annulare centrifugum typically presents annular shaped scaly patches on the edges of the erythematous plaques. In all cases both findings, clinical and histopathological should be considered when it comes to annular lesions which are frequently seen in daily routine.